Psychological Well-Being of Parents of Very Young Children With Type 1 Diabetes – Baseline Assessment - de Beaufort, Carine; Pit-ten Cate, Ineke M.; Schierloh, Ulrike; Cohen, Nathan; Boughton, Charlotte K.; Tauschmann, Martin; Allen, Janet M.; Nagl, Katrin; Fritsch, Maria; Yong, James; Metcalfe, Emily; Schaeffer, Dominique; et al. (Frontiers in Endocrinology, 2021)
Background: Type 1 diabetes in young children is a heavy parental burden. As part of pilot phase of the KIDSAP01 study, we conducted a baseline assessment in parents to study the association between hypoglycemia fear, parental wellbeing and child behavior. Methods: All parents were invited to fill in baseline questionnaires: hypoglycemia fear survey (HFS), WHO-5, Epworth Sleepiness Scale and Strength and Difficulties Questionnaire (SDQ). Results: 24 children (median age: 5-year, range 1-7 years, 63% male, mean diabetes duration: 3 ± 1.7 years) participated. 23/24 parents filled out the questionnaires. We found a higher score for the hypoglycemia fear behavior 33.9 ± 5.6 compared to hypoglycemia worry 34.6 ± 12.2. Median WHO-5 score was 16 (8 - 22) with poor well-being in two parents. Median daytime sleepiness score was high in five parents (>10). For six children a high total behavioral difficulty score (>16) was reported. Pro social behavior score was lower than normal in six children (<6). Parental well-being was negatively associated with HSF total (r = - 0.50, p <.05) and subscale scores (r = - 0.44, p <.05 for HSF-Worry and HSF-Behavior), child behavior (r = - 0.45, p = .05) and positively with child age (r = 0.58, p <.01). HSF, parental well-being nor daytime sleepiness are associated with the HbA1c. Conclusion: Regular screening of parental well-being, hypoglycemia fear and child behavior should be part of routine care to target early intervention.